Experience-dependent plasticity of multiple receptive field properties in lateral geniculate binocular neurons during the critical period - Pan, Meng; Ye, Jingjing; Yan, Yijing; Chen, Ailin; Li, Xinyu; Jiang, Xin; Wang, Wei; Meng, Xin; Chen, Shujian; Gu, Yu; Shi, Xuefeng (Frontiers in Cellular Neuroscience, 2025)
The visual thalamus serves as a critical hub for feature preprocessing in visual processing pathways. Emerging evidence demonstrates that experience-dependent plasticity can be revealed by monocular deprivation (MD) in the dorsolateral geniculate nucleus (dLGN) of the thalamus. However, whether and how this thalamic plasticity induces changes in multiple receptive field properties and the potential mechanisms remain unclear. Using in vivo electrophysiology, here we show that binocular neurons in the dLGN of 4-day MD mice starting at P28 undergo a significant ocular dominance (OD) shift during the critical period. This OD plasticity could be attributed to the potentiation of ipsilateral eye responses but not to the depression of deprived eye responses, contrasting with conventional observations in the primary visual cortex (V1). The direction and orientation selectivity of ipsilateral eye responses, but not of contralateral eye responses in these neurons, were dramatically reduced. Developmental analysis revealed pre-critical and critical period-associated changes in densities of both GABA positive neurons and GABAA receptor α1 subunit (GABRA1) positive neurons. However, early compensatory inhibition from V1 feedback in P18 MD mice maintained network stability with no changes in OD and feature selectivity. Mechanistically, pharmacological activation of GABAA receptors rescued the MD-induced OD shifts and feature selectivity impairments in critical period MD mice, operating independently of the V1 feedback. Furthermore, under different contrast levels and spatial frequencies, these critical period-associated changes in receptive field properties still indicate alterations in ipsilateral eye responses alone. Together, these findings provide novel insights into the developmental mechanisms of thalamic sensory processing, highlighting the thalamus as an active participant in experience-dependent visual plasticity rather than merely a passive relay station. The identified GABA-mediated plasticity mechanisms offer potential therapeutic targets for visual system disorders.